(untitled) (Veterinary Science, 2017)
It was made a phytochemical characterization of the leaves of Prosopisflexuosa var. flexuosa and Prosopis flexuosa var. depressa. The presence of flavonoids, triterpenes and steroidal groups, alkaloids and amino groups in both plant species was determined through the phytochemical progress. In the case of Prosopis flexuosa var. derpressa the presence of tannin was negative, but in the case of Prosopis flexuosa var. flexuosait was positive. Saponins regarding Prosopis flexuosa var. depressa showed lower surfactant power and more emulsifier power than Prosopis flexuosa var. flexuosa.